The impact of carer 'shared (disease management) responsibility' on 'shared decision making' for older persons managing multimorbidity - DINSMORE, JOHN; MURPHY, EMMA; HANNIGAN, CAOIMHE (My University, 2017)
Introduction: For older persons with multimorbidity (PwMs), self-management is a complex process that involves integration of knowledge and tasks for multiple, and often interacting, chronic diseases (1). Shared decision making (SDM) refers to clinicians working together with patients and/or their caregivers to decide which care plan best fits individual patients and their lives, when there is more than one reasonable option (2). The current study aimed to understand the role of caregiver support related to SDM for older PwMs (aged over 65). The data presented were collected as part of an extensive requirements gathering exercise to inform the design of ProACT, a digital health ecosystem that aims to support self-management and improve integration of care for older PwMs. Methods: Semi-structured qualitative interviews and focus groups were conducted with 38 older PwMs,17 informal carers and 22 formal care workers across the Irish and Belgian health systems. Interviews and focus groups were transcribed and analysed using thematic analysis. Results: PwMs in Belgium availed of higher levels of carer support and ‘shared responsibility’ for disease management with their carers. This was reported as having a potentially positive impact on SDM. Conclusion: Increased support from caregivers to PwMs may have a positive impact on improving SDM, due to the enhanced ‘shared responsibility’ between PwMs and carers to disease management. 1. Bayliss, E. A., Ellis, J. L., & Steiner, J. F. (2007). Barriers to self-management and quality-of-life outcomes in seniors with multimorbidities. Annals of Family Medicine, 5(5), 395–402. 2. Van der Flier, W.M., Kunnemann, M., Bouwman, F.H., Petersen, R.C., Smeets, E.M.A. (2017). Diagnostic dilemmas in Alzeimher’s disease: Room for shared decision making. Alzeimher’s and Dementia: Translational Research and Clinical Interventions, 3(3), 301-304.
European Journal of Neurology
3rd Congress of the European Academy of Neurology
PUBLISHED
Amsterdam, Netherlands
Keywords: Digital Health; Multimorbidity; Ageing; Chronic Disease; Ageing; Neuroscience; Age-related disability; Chronic Health Condition; Health